Targeting inflammation as a therapeutic strategy in accelerated atherosclerosis in rheumatoid arthritis. - Full, L; Monaco, C (2011)
Rheumatoid arthritis (RA) is an autoimmune disease affecting approximately 1% of the population. Patients have reduced life expectancy and the leading cause of death is cardiovascular disease (CVD), with patients experiencing at least a 2-fold increased risk of myocardial infarction. RA is recognized as an independent risk factor for CVD. Inflammation is a key contributor to the pathogenesis of atherosclerosis and cardiovascular events. As a common catalyst of both diseases, inflammation is the likely cause of increased prevalence of CVD in the RA population. Abating disease-related inflammation in RA may be an effective strategy in reducing CVD risk. Several other therapies used to modify cardiovascular risk factors in the general population such as statins and angiotensin-converting enzyme inhibitors are under investigation in patients with RA. This review discusses the parallels in the pathology of RA and atherosclerosis and discusses current therapies for RA and how they affect cardiovascular risk.